2016
DOI: 10.1093/bioinformatics/btw653
|View full text |Cite
|
Sign up to set email alerts
|

CLIP Tool Kit (CTK): a flexible and robust pipeline to analyze CLIP sequencing data

Abstract: cz2294@columbia.edu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
162
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(172 citation statements)
references
References 12 publications
1
162
0
Order By: Relevance
“…To this end, we took advantage of the computational approaches we previously developed to infer the precise protein-RNA crosslink sites from CLIP data by identifying crosslink-induced mutation sites (CIMS) and truncation sites (CITS) (Shah et al, 2017; Weyn-Vanhentenryck et al, 2014; Zhang and Darnell, 2011). We applied these methods to two in-depth LIN28 CLIP datasets: LIN28A HITS-CLIP performed in mouse ESCs (Cho et al, 2012), and LIN28B CLIP derived from two human cell lines K562 and HepG2 using a modified CLIP protocol named eCLIP (Van Nostrand et al, 2016) (for this study, we mainly describe results from K562 cells, as the results obtained from HepG2 cells are very similar).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, we took advantage of the computational approaches we previously developed to infer the precise protein-RNA crosslink sites from CLIP data by identifying crosslink-induced mutation sites (CIMS) and truncation sites (CITS) (Shah et al, 2017; Weyn-Vanhentenryck et al, 2014; Zhang and Darnell, 2011). We applied these methods to two in-depth LIN28 CLIP datasets: LIN28A HITS-CLIP performed in mouse ESCs (Cho et al, 2012), and LIN28B CLIP derived from two human cell lines K562 and HepG2 using a modified CLIP protocol named eCLIP (Van Nostrand et al, 2016) (for this study, we mainly describe results from K562 cells, as the results obtained from HepG2 cells are very similar).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the differences in protocols used to generate these CLIP libraries, we expected HITS-CLIP to capture only CIMS and eCLIP to be enriched in CITS (see Discussion). Following our established pipeline (Shah et al, 2017), we identified 50,292 substitution CIMS from LIN28A HITS-CLIP data and 22,673 CITS from LIN28B eCLIP data in K562 cells (Table S1). Consistent with the previous analysis (Cho et al., 2012), we observed a striking enrichment of the GGAG motif at CIMS inferred from HITS-CLIP data (11.5 fold at position 0), indicating the predominant crosslinking of the first G of the GGAG motif (Figure 1B left panel and Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adaptor was trimmed by fastx_clipper fastx_toolkit (http://hannonlab.cshl.edu/fastx_tool-kit/). Low quality bases were filtered by fastq_filter.pl, a custom perl script from CLIP Tool Kit (CTK) [65] and reads shorter than 24 nt discarded. After trimming, reads without a barcode marker sequence or within large fragment (length > 60 nt) are discarded to eliminate unspecific RNA tags.…”
Section: Analysis Of Miclip-sequencing Datamentioning
confidence: 99%
“…Both replicates were concatenated before peak calling. Both traditional peak calling with Clip Tool Kit (CTK) (Shah et al, 2017) [https://zhanglab.c2b2.columbia.edu/index.php/Standard/BrdU-CLIP_data_analysis _using_CTK]as well as CIMS analysis (Moore et al, 2014) were performed.…”
Section: Sequencing and Analysis Of Clip Datamentioning
confidence: 99%